2014
DOI: 10.1111/ter.12113
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Re‐Os isotope signatures in pyrite throughout low‐T, high‐P eclogite facies metamorphism

Abstract: Pyrite in LT–HP eclogites from the western Tianshan orogenic belt yields a Re‐Os age of 378.1 ± 8.9 Ma, which is 30–70 Ma older than ages previously obtained for the same rocks using the Rb–Sr, Sm–Nd, Ar–Ar, U–Pb, and Lu–Hf isotope systems. The Tianshan LT–HP eclogite experienced temperatures of up to ~570 °C combined with pressures of up to 2.1 GPa during metamorphism. These conditions are below the transition of pyrite to pyrrhotite, which defines both pyrite stability and possibly its closure temperature fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…McCandless et al, 1993;Suzuki et al, 1993;Stein et al, 1998Stein et al, , 2001Selby et al, 2009;Ootes et al, 2010;van Acken et al, 2014) we recommend caution when interpreting Re-Os data from metamorphosed ultramafic rocks. As a result, neither whole-rock ultramafic samples nor single chromite grains provide a robust Re-Os record of age information in the Ujaragssuit nunât layered body, due to its complex metamorphic history.…”
Section: Re-187 Os Versus 190 Pt-186 Osmentioning
confidence: 95%
See 1 more Smart Citation
“…McCandless et al, 1993;Suzuki et al, 1993;Stein et al, 1998Stein et al, , 2001Selby et al, 2009;Ootes et al, 2010;van Acken et al, 2014) we recommend caution when interpreting Re-Os data from metamorphosed ultramafic rocks. As a result, neither whole-rock ultramafic samples nor single chromite grains provide a robust Re-Os record of age information in the Ujaragssuit nunât layered body, due to its complex metamorphic history.…”
Section: Re-187 Os Versus 190 Pt-186 Osmentioning
confidence: 95%
“…Such work has been crucial in establishing the Re-Os evolution of the PUM and enabling the calculation of Re-Os model ages for more ancient samples. Numerous studies of crustal rocks have demonstrated that phases such as molybdenite (McCandless et al, 1993;Suzuki et al, 1993;Stein et al, 1998Stein et al, , 2001Ootes et al, 2010), bornite (Selby et al, 2009), chalcopyrite (Selby et al, 2009) and pyrite (Selby et al, 2009;van Acken et al, 2014), which have high Re/Os, can retain pristine Re-Os systematics despite experiencing metamorphic grades as intense as eclogite facies (van Acken et al, 2014). Zhao et al, 2001;Rollinson et al, 2002).…”
mentioning
confidence: 99%
“…43.3 Ma (n = 9) could be taken as the Re-Os dating result for all the sulfide samples. The slightly large MSWD of our plotted data is possibly due to variation in the initial 187 Os/ 188 Os ratio or differential diffusion of Os between samples, however, the Re-Os age is nevertheless considered useful (Stein and Hannah, 2014;van Acken et al, 2014). In fact, Re-Os isochron ages with large MSWD (4-17) for pyrite, chalcopyrite and sphalerite have been previously reported (e.g.…”
Section: Resultsmentioning
confidence: 64%
“…It is difficult to directly obtain evidence of the exact timing of movement on a fault. In some sulfide minerals, the Re-Os isotopic system has a relatively high closure temperature, and remains stable during thermal metamorphism and deformation events; accordingly, it can be applied to place timing constraints on sulfide-bearing faults and ore deposits (Stein et al, 1998;van Acken et al, 2014)…”
Section: Age Of Fe-cu Sulfide and E-w Extensionmentioning
confidence: 99%
“…Pyrite is relatively fast oxidized under atmospheric or aquatic conditions [76]. However, under anoxic conditions pyrite has been shown to remain robust for billions of years even through post-mineralization thermal and metamorphic disturbances [77][78][79].…”
Section: Retentivity Of U-th-he System In Pyrite and Mineral Stabilitymentioning
confidence: 99%